Effects of impact modifiers and lamination processes on the damage property of transparent Poly(methyl methacrylate) cast sheet - Sriprachuabwong, Chakrit; Kreua-ongarjnukool, Narumol; Charmondusit, Kitikorn (Asia-Pacific Journal of Science and Technology, 2017)
This research investigates the influence of impact modifiers and lamination processes on the damage properties of the impact modified transparent Poly (methyl methacrylate) (PMMA) cast sheets with butadiene rubber (Poly (S-co-MMA)/BR) and semi-interpenetrating polymer networks (semi-IPNs) with Polyurethane (PU) by the falling weight impact testing method. The impact modified transparent PMMA cast sheets were prepared by bulk polymerization via casting process. The effect of lamination processes on the damage property of transparent PMMA cast sheet was studied by chemical and mechanical lamination processes of PMMA onto the Poly (S-co-MMA)/BR cast sheets and the PMMA/PU semi-IPNs cast sheets. It was found that the hardness and flexural strength of the impact modified transparent PMMA cast sheets decreased with increasing the impact modifiers content. However, the hardness and flexural strength increased when the impact modified transparent PMMA cast sheets were laminated with PMMA. The impact strength of the PMMA/PU semi-IPNs cast sheets was higher than that of Poly (S-co-MMA)/BR cast sheets and impact strength of the laminated cast sheets by mechanical process was higher than that of chemical process. The damage type of the impact modified transparent PMMA cast sheets laminated via chemical process was brittle. While, the ductile failure was observed on the impact modified transparent PMMA cast sheets laminated via mechanical process. Scanning electron micrograph of laminated Poly (S-co-MMA)/BR cast sheets by chemical process revealed harmonious two-layers. The morphology of the laminated PMMA/PU semi-IPNs sheets showed the absolutely separation at two-layers conjunction, which affected the mechanical property of impact modified PMMA cast sheets. The impact modified transparent PMMA cast sheets with PU illustrated the superior impact property than that of BR. The mechanical lamination process with PMMA would not only improve the impact property of the impact modified transparent PMMA cast sheets but also decrease the amount of impact modifier using in the impact modified transparent PMMA cast sheets production process, which will useful for the further improvement of process efficiency and cost reduction.